A study on morphometry of coracoid process of scapula in north Indian population - Verma, Usha; Singroha, Ritu; Malik, Preeti; Rathee, Suresh Kanta (International Journal of Research in Medical Sciences, 2017)
Background: Coracoid process is a part of scapula and plays an important role in shoulder function. It arises from the antero-lateral aspect of the scapula. The aim of our study is to record the various morphometric parameters of the coracoid process. Methods: The study was performed on 50 pairs of human scapula of known sex in Department of Anatomy at PGIMS Rohtak. The parameters recorded were length, breadth, thickness, height and types of coraco-glenoid space by using vernier calipers. These parameters were compared in both sexes on both the sides. Results: Type I (round bracket) coraco-glenoid space was found to be predominant. Statistically significant difference was noted in all four parameters between males and females except in thickness on right side. Though all the four parameters have higher values on right side in comparison to left side but the difference was statistically insignificant. Conclusions: The study provides valuable information regarding the role of these parameters in etiology of subcoracoid impingement syndrome which will be helpful in its management to the surgeons.